Customer Satisfaction and Local Economic Strength: Evidence from Village Credit Institution (LPD) in Banyuning Traditional Village, Buleleng - Ismayanti, Komang Kristina; Suarmanayasa, I Nengah; Meitriana, Made Ary (International Journal of Economics Development Research (IJEDR), 2025)
This study explores the determinants of customer satisfaction within the Village Credit Institution (LPD) of Banyuning Traditional Village, Buleleng, Bali, as a reflection of local economic empowerment. Specifically, this research analyzes the influence of service quality, institutional image, and promotional strategies on customer satisfaction. A causal quantitative research design was employed, with the study population consisting of 901 customers of LPD Desa Adat Banyuning. Using probability sampling and the Slovin formula, 100 respondents were selected. The data collection technique involved a structured questionnaire, and the data were analyzed using multiple linear regression analysis. The findings indicate that service quality, image, and promotion collectively have a significant impact on customer satisfaction. Furthermore, each variable—service quality, institutional image, and promotion—was found to have a positive and significant individual effect on customer satisfaction. These results underscore the importance of improving service delivery, enhancing institutional image, and implementing effective promotional efforts to maintain customer trust and loyalty, particularly in the context of increasing competition among financial institutions in semi-urban village areas.